ANALYSIS OF THE NEEDS FOR THE DEVELOPMENT OF SOCIAL STUDIES LEARNING RESOURCES BASED ON GOOGLE SITE LOCAL WISDOM OF SEWANGI ISLAND - Wahyudi Rakhman; Bambang Subiyakto; Syaharuddin Syaharuddin (Universitas Lambung Mangkurat, 2026)
The availability of contextual learning resources is essential for improving the quality of social studies education in elementary schools. However, many existing learning materials remain general in nature and provide limited integration of local cultural heritage and indigenous wisdom, reducing their relevance to students' social and cultural contexts. This study aims to analyze the need for social studies learning resources based on cultural heritage and local wisdom at SDN Berangas Barat 2 as a foundation for developing more contextual and meaningful instructional materials. A qualitative descriptive approach was employed to explore the perspectives and experiences of stakeholders regarding the availability and suitability of existing learning resources. Data were collected through classroom observations, semi-structured interviews with the school principal, two classroom teachers, and student representatives, as well as document analysis of the curriculum, teaching materials, and lesson plans. Data analysis followed an interactive model involving data reduction, data display, and conclusion drawing to identify key themes and patterns. The findings reveal that the current learning resources are predominantly textbook-oriented and have not adequately incorporated local cultural heritage and community wisdom into the learning process. Teachers expressed the need for contextual teaching materials that align with curriculum objectives while reflecting students' cultural environments. Students also demonstrated greater interest and engagement when learning activities were connected to familiar local contexts. These findings highlight the importance of developing culturally responsive social studies learning resources that integrate local heritage and wisdom. Such resources are expected to enhance students' conceptual understanding, strengthen cultural identity, promote character education, and support meaningful learning experiences in elementary social studies education.